Nanocrystalline boron-doped diamond nanoelectrode arrays for ultrasensitive dopamine detection. (10th December 2015) - Dincer, Can; Ktaich, Rabih; Laubender, Elmar; Hees, J. Jakob; Kieninger, Jochen; Nebel, Christoph E.; Heinze, Jürgen; Urban, Gerald A.
Graphical abstract: Highlights: BDD-NEAs for low-level dopamine detection without selective membrane are presented. DA detection at O-terminated BDD shows a signal largely independent of AA. Differential pulse voltammetry is employed to improve the DA sensitivity. Detection limit less than 100 nM under physiological conditions is achieved. Abstract: In this paper we present nanocrystalline boron-doped diamond nanoelectrode arrays (BDD-NEAs) for the low-level detection of biogenic substances such as dopamine (DA) without the need for a selective membrane. We achieved a sensitive and reproducible detection of dopamine in the presence of ascorbic acid (AA) with oxygen (O-) terminated BDD-NEAs. To improve the peak separation between dopamine and ascorbic acid, differential pulse voltammetry (DPV) was employed. Therewith, it was possible to measure dopamine with a sensitivity of 57.9 nA μM −1 cm −2 . The detection limit was less than 100 nM with a linear behavior up to a concentration of 20 μM. The choice of the appropriate termination, the combination of the advantages of nanoelectrode arrays together with the outstanding electrochemical properties of boron-doped diamond and the right measurement method allowed successful measurement of dopamine in physiological concentrations in the presence of ascorbic acid.